2003
DOI: 10.1038/sj.onc.1206791
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of TGF-β signaling through Smad2, Smad3 and Smad4

Abstract: Smad transcription factors mediate the growth inhibitory effect of transforming growth factor-b (TGF-b) in many cell types. Mutational inactivation of Smads has been correlated with loss of responsiveness to TGF-b-mediated signal transduction. In this study, we compare the contribution of individual Smads to TGF-b-induced growth inhibition and endogenous gene expression in isogenic cellular backgrounds. Smad2, Smad3 and Smad4 expression were selectively inhibited in differentiationcompetent cells by using impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 65 publications
7
101
0
1
Order By: Relevance
“…This antisense RNA:DNA hybrid oligonucleotides recruit RNaseH to the Smad2 or Smad3 target mRNA, causing its degradation. Several lines of evidence have indicated already that this RNaseH-mediated antisense strategy is a valid and alternative approach for siRNA-mediated depletion of gene products (15,25). Moreover, we have validated some of our results obtained with GBs also with the siRNA-based approach and the same results were obtained using either tool, except for the effect of Smad2 depletion on MMP-9 gene induction by TGFβ.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This antisense RNA:DNA hybrid oligonucleotides recruit RNaseH to the Smad2 or Smad3 target mRNA, causing its degradation. Several lines of evidence have indicated already that this RNaseH-mediated antisense strategy is a valid and alternative approach for siRNA-mediated depletion of gene products (15,25). Moreover, we have validated some of our results obtained with GBs also with the siRNA-based approach and the same results were obtained using either tool, except for the effect of Smad2 depletion on MMP-9 gene induction by TGFβ.…”
Section: Discussionsupporting
confidence: 83%
“…In accordance with our results obtained in the Nme cells used here, the data collected from these other cell types point to Smad3 as an essential mediator of responses to TGFβ. Three reports from studies in human epithelial cell lines, including keratinocytes or hepatocytes, showed that Smad3 also has a prominent role in TGFβ-mediated cell cycle arrest and apoptosis (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to TGF-b (Ling et al, 2002;Kretschmer et al, 2003;Siegel et al, 2003;Kowanetz et al, 2004), activin was identified as a novel regulator of Id gene expression. Similar to TGF-b, activin has opposite effects on keratinocytes and fibroblasts.…”
Section: Id Proteins In Epidermal Homeostasismentioning
confidence: 99%
“…In vitro studies have shown that TGF-␤-induced growth inhibition in epithelial cells is preferentially mediated by Smad3 (10,11) and that cyclin-dependent kinase (cdk) 2 and cdk4 can phosphorylate Smad3, thus inactivating its ability to instigate cell cycle arrest (12). Therefore, Smad3 may mediate TGF-␤1-induced growth inhibition during cancer development.…”
Section: Introductionmentioning
confidence: 99%